2018
DOI: 10.1111/nmo.13296
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal dysmotility according to Chicago classification v3.0 vs v2.0: Implications for association with reflux, bolus clearance, and allograft failure post‐lung transplantation

Abstract: Irrespective of CC used, o-CLAD appears linked to EGJOO. CCv2.0 however, accentuates the increased reflux and incomplete bolus transit associated with hypo-contractility post-LTx, suggesting that these motor abnormalities, though considered minor, may be of importance after lung transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…These observations support our previous findings that minor peristaltic abnormalities not classified as abnormal by CCv3.0 can associate with increased reflux exposure in respiratory patients. [14,15] In contrast, in IPF patients with normal motility, DCI strongly and inversely correlated with the proportion of reflux events reaching the proximal esophagus, a relationship not seen with total reflux exposure, likely because the inter-patient variation in DCI will be small in patients with normal motility and tLESRs appeared to be not increased. Thus, in patients with respiratory disease, such as IPF, ineffective esophageal peristaltic events, along with potentially other motor features not measured in this study, such as abnormal esophageal tone and post-reflux swallow-induced peristaltic wave (PSPW) index, may be associated with poor clearance and proximal migration of reflux events, possibly aided by factors not present in patients with GERD only, such as greater negative intra-thoracic pressure.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These observations support our previous findings that minor peristaltic abnormalities not classified as abnormal by CCv3.0 can associate with increased reflux exposure in respiratory patients. [14,15] In contrast, in IPF patients with normal motility, DCI strongly and inversely correlated with the proportion of reflux events reaching the proximal esophagus, a relationship not seen with total reflux exposure, likely because the inter-patient variation in DCI will be small in patients with normal motility and tLESRs appeared to be not increased. Thus, in patients with respiratory disease, such as IPF, ineffective esophageal peristaltic events, along with potentially other motor features not measured in this study, such as abnormal esophageal tone and post-reflux swallow-induced peristaltic wave (PSPW) index, may be associated with poor clearance and proximal migration of reflux events, possibly aided by factors not present in patients with GERD only, such as greater negative intra-thoracic pressure.…”
Section: Discussionmentioning
confidence: 89%
“…Following at least a 30s baseline to identify the upper esophageal sphincter (UES) and LES, ten 5 ml saline swallows were given at least 30s apart with the patient supine. [14,15] HRIM recordings were analyzed manually, blinded to pulmonary function data, using appropriate dedicated software (ManoView Analysis Software v3.01, Medtronic Inc., Shoreview, MN or Solar GI HRM, MMS, Enschede, The Netherlands). CCv3.0 algorithms were applied to make a diagnosis of normal or an esophageal motility disorder.…”
Section: Hrimmentioning
confidence: 99%
“…Irrespective of Chicago Classification used, only patients with esophagogastric junction outflow obstruction appeared more likely to develop allograft dysfunction than those with normal motility (P<0.05). Thus, the identification of more subtle abnormalities of hypocontractility (and therefore incomplete bolus transit and increased reflux) highlighted in Chicago classification v2.0 may have important consequences of allograft failure post-lung transplantation (19).…”
Section: Esophageal Disease After Lung Transplantationmentioning
confidence: 99%
“…Tagaroonsanti et al used HRIM to demonstrate that esophagogastric junction outflow obstruction (EGJOO), incomplete bolus clearance (IBC), and proximal reflux were risk factors for CLAD (98). They also reported that hypo-contractility on HRIM (defined by the Chicago classification v2.0) was associated with IBC and abnormal number of reflux events, both previously implicated in CLAD (99). Outflow obstruction in conjunction with abnormal bolus clearance perpetuate esophageal stasis and delayed esophageal acid clearance, therefore increasing the risk of aspiration.…”
Section: Motility Considerations In Lung Transplantmentioning
confidence: 99%